Performance of cross-border acquisitions: Evidence from China - FAN, Yuanyuan (Institutional Knowledge at Singapore Management University, 2020)
The number of cross-border mergers and acquisitions (M&As) in China has increased dramatically in recent years. Under China’s “go global” strategy, Chinese firms are devoting more capital and time to developing their overseas business. Cross-border M&As make up a large proportion of these activities. Therefore, it is crucial to determine what factors affect the performance of cross-border acquisitions. Previous studies show that the acquirers’ post-merger performance is affected by various factors. Those papers mainly focus on domestic M&As. However, cross-border M&As also have unique features. In this study, I focus on Chinese cross-border acquisitions and the factors that affect the acquirers’ post-merger performance. I start my research with a few case studies. I analyze Chinese cross-border acquisition deals and compare them with U.S. deals. In addition, I examine one domestic acquisition of a Chinese corporation and compare it with cross-border acquisitions conducted by Chinese acquirers. I find that post-merger integration for cross-border acquisitions faces more issues than that for domestic acquisitions. Through the case analysis, I identify two factors that are crucial to the post-merger performance of the acquirer. These two factors are due diligence and cultural conflicts. In the second part of my study, I conduct a series of empirical analyses. I use two proxies that are highly correlated with the due diligence process and culture conflicts to examine their impact on post-merger performance. I manually match data on Chinese cross-border deals from the Securities Data Company database to data from the China Stock Market and Accounting Research database. The empirical results show that acquirers’ overseas experience is associated with better post-merger performance and market reactions. Moreover, the deal characteristics differ between targets incorporated in developed and developing countries. However, long-term post-merger performance does not vary with the target incorporated nation. To conclude, my study shows that firms undertaking cross-border acquisitions need to conduct thorough due diligence and pay more attention to post-merger integration. Although the market might have different reactions to the acquisitions of firms incorporated in different countries, long-term performance is not affected by the target’s nationality.